The epidemiology of fighting in group-housed laboratory mice - Theil, Jacob H. (Sci Rep, 2020)
Injurious home-cage aggression (fighting) in mice affects both animal welfare and scientific validity. It is arguably the most common potentially preventable morbidity in mouse facilities. Existing literature on mouse aggression almost exclusively examines territorial aggression induced by introducing a stimulus mouse into the home-cage of a singly housed mouse (i.e. the resident/intruder test). However, fighting occurring in mice living together in long-term groups under standard laboratory housing conditions has barely been studied. We performed a point-prevalence epidemiological survey of fighting at a research institution with an approximate 60,000 cage census. A subset of cages was sampled over the course of a year and factors potentially influencing home-cage fighting were recorded. Fighting was almost exclusively seen in group-housed male mice. Approximately 14% of group-housed male cages were observed with fighting animals in brief behavioral observations, but only 14% of those cages with fighting had skin injuries observable from cage-side. Thus simple cage-side checks may be missing the majority of fighting mice. Housing system (the combination of cage ventilation and bedding type), genetic background, time of year, cage location on the rack, and rack orientation in the room were significant risk factors predicting fighting. Of these predictors, only bedding type is easily manipulated to mitigate fighting. Cage ventilation and rack orientation often cannot be changed in modern vivaria, as they are baked in by cookie-cutter architectural approaches to facility design. This study emphasizes the need to invest in assessing the welfare costs of new housing and husbandry systems before implementing them.